Brief Report: Effects of Tenofovir and Amphotericin B Deoxycholate Coadministration on Kidney Function in Patients Treated for Cryptococcal Meningitis. (1st January 2016) - Kiggundu, Reuben; Morawski, Bozena M.; Bahr, Nathan C.; Rhein, Joshua; Musubire, Abdu K.; Williams, Darlisha A.; Abassi, Mahsa; Nabeta, Henry W.; Hullsiek, Kathy H.; Meya, David B.; Boulware, David R.
Abstract : Abstract: The effect of tenofovir and amphotericin coadministration on kidney function is poorly characterized. We measured creatinine during induction therapy and at 4 weeks after diagnosis in Ugandans undergoing cryptococcal meningitis therapy and classified as not receiving antiretroviral therapy (ART), receiving nontenofovir ART or receiving tenofovir-based ART. Longitudinal creatinine changes and grade 2–4 creatinine adverse events were evaluated across groups. Creatinine concentrations were similar across ART groups. At 4 weeks after diagnosis, creatinine was 0.25 mg/dL higher than at diagnosis, but similar across groups. Adverse event incidence was also similar across ART groups. Tenofovir and amphotericin coadministration did not increase the risk of kidney dysfunction.